Developing economies and the Asia-Pacific economic cooperation forum-APEC: intrabloc trade and attraction of foreign direct investment from region - Rodríguez, Christian (2008)
Since one of the main goals of the APEC is to facilitate the international trade and investments among its members, it is said that taking over APEC presidency (as Peru in 2008), will contribute to foster trade and attract investments from member economies. But, is there any pattern which allows quantifying the benefi ts resulting from this kind of commitment? After evaluating the trade statistics of APEC developing economies ever since the creation of the Forum in 1989, it can be inferred that presiding APEC does not guarantee an increase in its trade with the rest of APEC economies. Right after hosting the summit, its imports grow higher compared with its exports, but there is not any conclusive information on the growth of foreign direct investment (FDI). Nevertheless, even though the growth of trade and FDI attraction from APEC other member economies does not rely exclusively on taking over the Forum’s Presidency, this commitment is a unique opportunity to promote trade with the planet’s most important economic bloc.